Reliability Evaluation of Transformer Oil Insulation with H2O Water and Super O2 Water Contaminants Disaster Mitigation Electrical Engineering - Christiono R; Iwa Garniwa; Miftahul Fikri; Andi Amar Thahara (Sultan Publisher, 2022)
Transformer oil insulation failure is one of them that can cause water to penetrate through the mechanical acrylic cap on the OLTC (on load tap changer) which causes contaminants in the transformer insulation oil which affects the reliability of the transformer until there is damage to the transformers widely. For this reason, research was carried out to evaluate the reliability of transformer oil insulation with contaminants of H2O water and Super O2 water. This study is to evaluate the effect of water contaminants with experimental methods using BAUR Oil Tester test equipment, with H2O water and super O2 as samples of water contaminants on transformer oil insulation. According to SPLN 49-1: 1982, the standard value of breakdown voltage in insulating oil is ≥30kV/2.5mm. Then, 1ml of H2O water will be given so that a decrease in the breakdown voltage value of 31.5% is obtained and this experiment is carried out up to 10ml, which means that the more H2O is given, the value of the breakdown voltage is further away from the SPLN standard. Meanwhile, insulating oil contaminated with super O2 water obtained a breakdown voltage of 68% which means that the more super O2 water, the more the reliability of transformer oil insulation decreases, and the breakdown voltage value also decreases which adversely affects the reliability of the transformer.